Development of Contextual Based Electronic Global Warming Modules Using Flipbook Applications as Physics Learning Media in High Schools - Neneng Susanti; Yennita Yennita; Azhar Azhar (Journal of Educational Sciences, 2020)
This study aims to produce physics learning media in high schools in the form of the development of contextual based electronic global warming modules using a valid, practical and effective flipbook application. This type of research is research and development using the ADDIE model (Analysis, Design, Development, Implementation and Evaluate). The field trial design used was One Group Pretest-Posttest Design. The development of contextual based electronic global warming modules using the flipbook application has passed the validation test stage with an average percentage of material experts at 88.42% with a very valid category and an average percentage of media experts at 85.63% with a very valid category. Practicality test by the teacher obtained an average percentage score of 85.56% with very practical criteria and by students obtained an average percentage score of 91.33% with a very practical category. Improved learning outcomes using e-modules and without e-modules (the results of last year's tests) are included in the increased category. It can be concluded that the use of contextual-based electronic modules using the flipbook application in learning can improve student physics learning outcomes.